MiRNA505/NET1 Axis Acts as a CD8(+) T-TIL Regulator in Non-Small Cell Lung Cancer - Zhu, Pengyuan (Onco Targets Ther, 2020)
INTRODUCTION: Lung adenocarcinoma (LUAD), which is the most important and common subtype of non-small cell lung cancer (NSCLC), is highly heterogeneous with a poor prognosis and poses great challenges to health worldwide. MicroRNAs (miRNAs) are regulators of gene expression with recognized roles in physiology and diseases, such as cancers, but little is known about their functional relevance to CD8(+) T cell infiltration regulation in the tumor microenvironment (TME) of NSCLC patients, especially LUAD patients. METHODS: Bioinformatic analysis was used to analyze TCGA data. RT-PCT, Western blot, luciferase assay and immunohistochemistry were used to detect the expression levels and bindings of genes and miRNA. ELISA and cytotoxic assay were used to evaluate CD8(+) T cell function. RESULTS: In this study, bioinformatic analysis unveiled the miR-505-3p/NET1 pair as a CD8(+) T-tumor-infiltrating lymphocyte (TIL) regulator. Then, we confirmed the bioinformatic results with LUAD patient samples, and NET1 was shown to be a direct target of miR-505-3p in a luciferase assay. Functional experiments demonstrated that miR-505-3p enhanced CD8(+) T-TIL function, while NET1 impaired CD8(+) T-TIL function and partly reversed the effects of miR-505-3p. The observed effects might be exerted via the regulation of immunosuppressive receptors in T cells. DISCUSSION: Our study may provide novel insights into LUAD progression related to the TME mechanism and new possibilities for improving adoptive immunotherapy.